The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/09687688.2017.1393566
|View full text |Cite
|
Sign up to set email alerts
|

K+-Clco-transporter 2 (KCC2) – a membrane trafficking perspective

Abstract: K-Cl co-transporter 2 (KCC2/SLC12A5) is a neuronal specific cation chloride co-transporter which is active under isotonic conditions, and thus a key regulator of intracellular Cl levels. It also has an ion transporter-independent structural role in modulating the maturation and regulation of excitatory glutamatergic synapses. KCC2 levels are developmentally regulated, and a postnatal upregulation of KCC2 generates a low intracellular chloride concentration that allows the neurotransmitters γ-aminobutyric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…The activity of KCC2 is regulated not only by expression level but also through various other mechanisms, such as phosphorylation/de-phosphorylation [130][131][132] and membrane trafficking [133][134][135]. For example, phosphorylation of threonine residues 906 and 1007 decreases the activity of KCC2.…”
Section: Developmental Changes In Gabaergic and Glycinergic Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of KCC2 is regulated not only by expression level but also through various other mechanisms, such as phosphorylation/de-phosphorylation [130][131][132] and membrane trafficking [133][134][135]. For example, phosphorylation of threonine residues 906 and 1007 decreases the activity of KCC2.…”
Section: Developmental Changes In Gabaergic and Glycinergic Actionmentioning
confidence: 99%
“…The phosphorylation of tyrosine residue 1087 is involved in internalization of KCC2, which results in the down-regulation of KCC2 activity [135]. In addition to tyrosine residue phosphorylation, other complex mechanisms may play roles in trafficking and endocytosis of KCC2 and regulate the activity of KCC2 in developing neurons [133][134][135].…”
Section: Developmental Changes In Gabaergic and Glycinergic Actionmentioning
confidence: 99%
“…The authors showed with co-transfection experiments that full-length APP, but not its proteolytic fragments, stabilized KCC2 levels. Functional expression of KCC2 at the neuronal cell surface is necessary for its Cl − efflux activity, and the trafficking of KCC2 to the cell surface and its subsequent endocytic internalization is regulated by different cellular mechanisms, with defects in these known to underlie a range of neuropathological conditions [58]. One such regulatory mechanism is the tyrosine phosphorylation of KCC2 mediated by tyrosine kinases, such as Src [81,82,83], which promotes KCC2 internalization from the plasma membrane and its subsequent lysosomal degradation.…”
Section: App’s Modulation Of Gabaergic Neurotransmission Through Pmentioning
confidence: 99%
“…GABA A R functions as ligand-gated chloride (Cl − ) channels and whether GABA binding would be depolarizing or hyperpolarizing is largely determined by intracellular Cl − concentrations and the GABA reversal potential (E GABA ). Resting Cl − concentration in central nervous system (CNS) neurons is determined by the activity of two major cation-chloride cotransporters, namely the Cl − influx-mediating Na + -K + -2Cl − cotransporter 1 (NKCC1) and the efflux-mediating K + -Cl − cotransporter 2 (KCC2) [58]. In the adult brain, GABA is mainly hyperpolarizing and inhibitory, but it is primarily depolarizing and excitatory in developing neurons, as demonstrated using rat embryonic and neonatal cortical slices [59].…”
Section: Introductionmentioning
confidence: 99%
“…KCC2 transcript levels could be downregulated by neuronal activity [11,12] and brain-derived growth factor (BDNF)-TrkB signaling [13], and its post-translational functional activity is mainly determined by the level of expression at the plasma membrane. The 12-transmembrane KCC2 protein oligomerises, and its membrane trafficking [14], as well as "diffusion-trapping" [15] at the plasma membrane is modulated by neuronal activity-dependent phosphorylation/dephosphorylation of key serine and threonine residues at its cytoplasmic loops. Phosphorylation of S940 of KCC2 by protein kinase C (PKC) [16], for example, is known to stabilize KCC2 at the cell surface and reduces its internalization, whereas excitatory input through the NMDA receptor dephosphorylate S940 by protein phosphatase 1 (PP1) [12] downregulates KCC2's Cl − efflux activity.…”
Section: Introductionmentioning
confidence: 99%